KUALITAS AIR SERTA PERILAKU MASYARAKAT DALAM MENGELOLA LIMBAH PADAT DAN AIR LIMBAH DI SUNGAI AYUNG, KELURAHAN KESIMAN PETILAN KOTA DENPASAR - I G H Purnama; M A H Suryadhi Suryadhi; N L M A S S B Rahmi (Program Studi Biologi Universitas Udayana, 2024)
Based on the development plan for Kesiman Petilan Village, Ayung River, starting from the Bridge on Jalan Sulatri to the Balitex Bridge on Jalan WR. Supratman – Denpasar City, will be arranged into a new water tourism spot. This new tourist location will contain water sports, restaurants, fishing spots and so on. The study aims to analyze the health risks of the bacteriological quality of water passing through the two segments of the Ayung River, as well as to examine the content of heavy metals Lead (Pb), Cadmium (Cd), in sediments and fish caught in the river, as well as to determine the behavior of the surrounding community in managing solid waste and waste water. The study uses a quantitative descriptive design. The results showed that overall, the content of Coliform and Escherichia coli in the Ayung River segment was above 10,000 MPN/100mL, far exceeding the quality standard allowed in Bali Governor Regulation Number 16 of 2016 concerning Environmental Quality Standards and Environmental Pollution Standard Criteria, especially in water, for water recreation tourism in Class II, which is 1000MPN/100mL, so that the water of the Ayung River is bacteriologically polluted. Likewise, the heavy metal content in river sediments exceeds the permissible standard. The content of heavy metals in caught fish and shrimp is still below the Indonesian National Standard (SNI) 7387 of 2009 concerning the maximum limit of heavy metal contamination in food. In addition, people's behavior in disposing of solid waste and household waste water around the Ayung River still needs to be improved so as not to pollute the environment and the Ayung River. Therefore, efforts are needed to further deepen public knowledge and awareness in preserving the Ayung River. Keywords: bacteriological, heavy metal, garbage, liquid waste, behavior, Ayung River